Complexation and transport of alkali and alkaline earth metal cations by p-tert-butyldihomooxacalix[4]arene tetraketone derivatives (vol 18, pg 2, 2006) - Marcos, PM (2015)
The binding properties of three p-tert-butyldihomoox-acalix[4]arene tetraketone derivatives (tert-butyl 2b, adamantyl 2c and phenyl 2d) in the cone conformation and one derivative (methyl 2a) in a partial cone conformation, towards alkali and alkaline earth metal cations have been established by extraction studies of metal picrates from water into dichloromethane, stability constant measurements in methanol and acetonitrile, and by H-1 NMR spectrometry. Transport experiments of metal picrates through a dichloromethane membrane were also performed. The results are compared to those obtained with closely-related calix[n]arene derivatives (n = 4 and 5) and discussed in terms of the substituents, size and conformational effects. Methylketone 2a is a poor binder for all the cations studied, due to its partial cone conformation. Ketones 2b, 2c and 2d show high extraction and complexation levels for the alkali cations, with similar profiles and preference for K+ and Na+ (plateau selectivity). Towards alkaline earth cations, these ketones show a strong peak selectivity for Ba2+ in extraction, but a plateau selectivity for Ca2+, Sr2+ and Ba2+ in complexation. The nature of the substituent attached to the ketone function has some influence on their binding properties, with phenylketone 2d being a slightly weaker binder than ketones 2b and 2c. 1H NMR titrations confirm the formation of 1:1 complexes between the ketones and the cations studied, also indicating that they should be located inside the cavity defined by the phenoxy and carbonyl oxygen atoms. Ketones 2b, 2c and 2d show transport rates that do not follow, in general, the same trends observed in extraction and complexation.